GREENING PUBLIC SERVICE PERFORMANCE: THE INTERPLAY OF GREEN LEADERSHIP AND ENTREPRENEURIAL LEADERSHIP CHARACTERISTICS THROUGH A GREEN INNOVATION CLIMATE - Gustina, Evi; Aurora Lubis, Tona; Masriani, Ida (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study examines the influence of Green Leadership and Entrepreneurial Leadership Characteristics on Public Service Performance, with Green Innovation Climate as a mediating variable at the Environmental Agency of Jambi Province. Drawing upon Natural Resource-Based View (NRBV), Upper Echelons Theory (UET), Public Sector Entrepreneurship (PSE), and Organizational Climate theory within the AMO framework (Ability–Motivation–Opportunity), this research proposes an integrated model linking leadership orientation, innovation climate, and public service outcomes. The study employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from civil servants and contract employees across organizational units. The findings indicate that Green Leadership and Entrepreneurial Leadership Characteristics significantly influence Green Innovation Climate. Green Innovation Climate significantly affects Public Service Performance and mediates the relationship between leadership variables and service performance. These findings suggest that environmentally oriented and entrepreneurial leadership can strengthen organizational climate for green innovation, which in turn enhances program achievement, service quality, stakeholder coordination, regulatory compliance, and environmental impact.